Analisis Minat Belajar Matematika Berbasis Game Simulation Ditinjau dari Gender Siswa Kelas VII SMP Buti - Ahmad Supendi; Mutiya Oktariani (Politeknik Negeri FakFak, 2025)
This research is motivated by the fact that students at SMP Negeri Buti show varying levels of learning interest, with some having high interest and others low. Interviews with the mathematics teacher revealed that overall student interest is low, especially among male students who tend to be disruptive during lessons. Therefore, the researcher aimed to explore students' interest in learning mathematics through game simulation-based learning, viewed from a gender perspective. This descriptive qualitative study involved 30 eighth-grade students at SMP Negeri Buti as research subjects. Data were collected through observation, questionnaires, and documentation. The results showed that most students did not pay attention to the teacher’s explanations, and there were gender-based differences in learning interest among seventh-grade students, with male students showing higher interest than female students. It was concluded that overall, the eighth-grade students at SMP Negeri Buti demonstrated a very low level of learning interest. owever, after the implementation of the simulation game, there was a significant increase in interest in learning.